Editorial for issue 3-2017: 65 years of the Military Technical Courier – acknowledgments - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This editorial marks the jubilee which the scientific journal Military Technical Courier celebrates in 2017 - 65 years of regular and continuous publication. On this occasion, the Editorial Office expresses gratitude to individuals and institutions who have contributed most to the progress and success of the journal.